Maple Leaf City. Un immaginario biomeccanico per ri-abitare la città - Golino, Antonella; Panunzi, Stefano (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Maple Leaf City. A biomechanical imaginary to re-inhabit the city The aim of the paper is to describe an interdisciplinary project carried out by the Aria Center (Research Center for Internal Areas and Appennines) of the University of Molise with a view to re-signifying the city of Campobasso, in Molise. The essay explores the urban imagination of Campobasso starting from the recovery of the enigmatic name, Maple Leaf City, given to it by the Canadian occupation in World War II. This work illustrates the recursive and random generation of events, chronotopes in the space-time ecosystem of Campobasso, with the first resonances triggered for now in the social and political fabric. The action began in 2013 and is inter-institutional and interdisciplinary, in ever-changing configurations, coupled with relevant dates and initiatives, but not specific, different for media coverage and target audience, with heterogeneous communication practices: urban performances, conferences, workshops, competitions, interviews, social networks, lessons for elementary school children or university students. The aim of the work is therefore to describe a process of de- and re urbanization of the city, aimed at re-conceptualizing the city. The description in question shows that today we are witnesses of transformations that deeply affect the territory, such as to change the perception of time, space and the relative attribution of meanings to the city as a place.